Final 5-year findings from the phase 3 HELIOS study of ibrutinib plus bendamustine and rituximab in patients with relapsed/refractory chronic lymphocytic leukemia/small lymphocytic lymphoma. Issue 13 (9th November 2020) - Fraser, Graeme A.M.; Chanan-Khan, Asher; Demirkan, Fatih; Santucci Silva, Rodrigo; Grosicki, Sebastian; Janssens, Ann; Mayer, Jiri; Bartlett, Nancy L.; Dilhuydy, Marie-Sarah; Loscertales, Javier; Avigdor, Abraham; Rule, Simon; et al.
Abstract: We report final analysis outcomes from the phase 3 HELIOS study (NCT01611090). Patients with relapsed/refractory chronic lymphocytic leukemia/small lymphocytic lymphoma without deletion 17p ( n = 578) were randomized 1:1 to 420 mg daily ibrutinib or placebo plus ≤6 cycles of bendamustine plus rituximab (BR), followed by ibrutinib or placebo alone. Median follow-up was 63.7 months. Median investigator-assessed progression-free survival was longer with ibrutinib plus BR (65.1 months) than placebo plus BR (14.3 months; hazard ratio [HR] 0.229 [95% confidence interval (CI) 0.183–0.286]; p < .0001). Despite crossover of 63.3% of patients from the placebo plus BR arm to ibrutinib treatment upon disease progression, ibrutinib plus BR versus placebo plus BR demonstrated an overall survival benefit (HR 0.611 [95% CI 0.455–0.822]; p = .0010; median not reached in either arm). Long-term follow-up data confirm the survival benefit of ibrutinib plus BR over BR alone. Safety profiles were consistent with those known for ibrutinib and BR.